2015
DOI: 10.1002/asi.23595
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory information searching in the enterprise: A study of user satisfaction and task performance

Abstract: No prior research has been identified that investigates the causal factors for workplace exploratory search task performance. The impact of user, task, and environmental factors on user satisfaction and task performance was investigated through a mixed methods study with 26 experienced information professionals using enterprise search in an oil and gas enterprise. Some participants found 75% of high-value items, others found none, with an average of 27%. No association was found between self-reported search ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 109 publications
(112 reference statements)
2
19
0
Order By: Relevance
“…The time required to analyse the large amount of information causes uneasiness and lowers confidence in information use. These findings are in line with recent research that suggests that information overload may influence the ability to search information effectively, and that people may not be aware of this (see Cleverley, ; Cleverley, Burnett & Muir, ). This could lead to search tasks being terminated early and with a detrimental effect on organisational outcomes (Cleverley, Burnett & Muir, ).…”
Section: Discussionsupporting
confidence: 90%
“…The time required to analyse the large amount of information causes uneasiness and lowers confidence in information use. These findings are in line with recent research that suggests that information overload may influence the ability to search information effectively, and that people may not be aware of this (see Cleverley, ; Cleverley, Burnett & Muir, ). This could lead to search tasks being terminated early and with a detrimental effect on organisational outcomes (Cleverley, Burnett & Muir, ).…”
Section: Discussionsupporting
confidence: 90%
“…Increasing information volumes were identified as a factor for increasing dissatisfaction [section 4.3] supporting existing studies [38,97] although models for information system success only mention the quality property of information, which provides widespread opportunities to revise models in the literature (such as DeLone and McLean [64]). …”
Section: Discussionmentioning
confidence: 77%
“…First, in contrast to web search, the hybrid strategy fits high performing organizations who apply human and machine resources to effect strategic information outcomes, despite an environment of exponential data growth (information overload) and severe time constraints. By serialization, the strategy overcomes the low quality of applying exploratory search alone (Cleverley et al, , p. 92) and the low quality of applying directed browsing alone (see rough calculation above), thus increasing the yield of relevant files.…”
Section: Resultsmentioning
confidence: 99%
“…Cleverley, Burnett, and Muir () concluded that organizations faced with information overload “may not ‘know’ they ‘don't know’” that they are missing high value information (pp. 1, 93).…”
Section: Discussionmentioning
confidence: 99%